Reduction of Train-Induced Vibration in Buildings - Talbot, J.P. (Engineering Transactions, 2015)
There are many ways of reducing the transmission of train-induced vibration into buildings. One such measure is the use of floating-slab track whereby the track is mounted on a concrete foundation resting on isolation bearings. Impressive claims are often made regarding its effectiveness by referring to simple mass-spring models. However, some recent work, reviewed in the initial part of this paper, suggests that the effectiveness of floating-slab track for underground railways can be severely limited by interactions with the tunnel and surrounding soil. The paper goes on to discuss base isolation of buildings as an alternative to vibration countermeasures at source. Again, simple mass-spring models are often used to make predictions of isolation performance which are far too optimistic. Alternative models are discussed with a view to developing a more appropriate means of assessing isolation performance.